Thermal oxidation of amorphous germanium thin films on SiO2 substrates. (11th November 2016) - de los Santos Valladares, L; Dominguez, A Bustamante; Ionescu, A; Brown, A; Sepe, A; Steiner, U; Quispe, O Avalos; Holmes, S; Majima, Y; Langford, R; Barnes, C H W
Abstract: In this work we report the thermal oxidation of amorphous germanium ( a -Ge) thin films (140 nm thickness) in air. Following fabrication by conventional thermal evaporation on SiO2 substrates, the samples were annealed in air at different temperatures ranging from 300 to 1000 °C. By means of x-ray diffraction, x-ray reflectivity, synchrotron grazing-incidence wide-angle x-ray scattering and cross-sectional transmission electron microscopy analysis it is found that the a -Ge films abruptly crystallize at 475 °C, while simultaneously increasing the thickness of the oxide (GeO2 ) in a layer by layer fashion. X-ray photoemission spectroscopy reveals that the oxidation state of the Ge atoms in the GeO2 layer is 4 + . However, a reaction at the GeO2 /Ge interface occurs between 500 and 550 °C reducing the oxide layer to GeO x ( x < 2) and containing Ge 2+ and Ge + . The thickness of the oxide layer grows with the annealing temperature following an Arrhenius behavior with an activation energy of 0.82 ± 0.09 eV up to 500 °C. Remarkably, we observed simultaneous enhancement of the oxidation and crystallization of the a -Ge in the temperature interval 450 °C–500 °C, in which the oxidation rate reaches a maximum of around 0.8 nm °C −1 at around 500 °C.